Assessing the impacts of “Feed-in tariffs Vs. Net metering” in deploying solar market in Egypt - Elsayed, Mostafa (AUC Knowledge Fountain, 2017)
In recent years, Egypt isn’t only experiencing one of its hardest fuel shortages and blackouts,with the country’s deficiency in supplying industries and communities with the needed power (Kandil, Saadawi, Saeed, & Hassan, 2015) But also, in the last three decades the consumption of electric energy rate has increased on average 7% per year in Egypt. Hence, diversification of energy sources such as renewable energy technologies application is inevitable to satisfy the continuous demand on energy (El-Kholy&Faried, 2011). Egypt started initiating renewable energy strategy, which aims to rise the dependency on renewable energies up to 20% of the total energy production by 2020 (Kandil, Saadawi, Saeed, & Hassan, 2015). Thus, in this study, it will measure the impact of different solar electricity approaches “Feed in tariffs Vs. Net metering” for the highest residential electricity tier, to tackle the effect of each on spreading the implementation of solar energy in the Egyptian market. The pros and cons of each approach is examined in order to estimate which approach is the optimal for Egypt’s circumstances. Ultimately, the mathematical calculations showed very promising results in favor of net metering for householders in offsetting their electricity bills. Still, this study suggests some recommendations for the Egyptian net metering scheme to avoid other countries’ mistakes.